THE EFFECT OF FERMENTATION TIME OF PAPAYA LEAVES (Carica papaya) ON THE GROWTH AND SURVIVAL RATE OF NILE TILAPIA (Oreochromis niloticus) - Joy Steven Emmanuel; I Nyoman Dodik Prasetia; Jasmine Masyitha Amelia; Gressty Sari Br Sitepu (Universitas Mataram, 2026)
Tilapia (Oreochromis niloticus) aquaculture has high economic value and rapid growth; however, the high cost of commercial feed necessitates the use of more economical and nutritionally adequate alternative feed ingredients, such as fermented papaya leaves (Carica papaya). This study aimed to evaluate the effect of different fermentation durations of papaya leaves in commercial feed on the growth and survival rate of tilapia and to determine the optimal fermentation time. This study employed an experimental method using a Completely Randomized Design (CRD) consisting of four treatments and three replications: treatment A (control without fermentation), treatment B (3 days fermentation), treatment C (5 days fermentation), and treatment D (7 days fermentation). Tilapia fingerlings measuring ±5–7 cm with an initial weight of ±3–4 g were reared for 30 days at a stocking density of 20 fish per tank. The observed parameters included weight gain and survival rate, while the water quality parameters measured were temperature, pH, dissolved oxygen (DO), and ammonia. The data were analyzed using a One-Way ANOVA test followed by Duncan’s multiple range test. The results showed that the addition of fermented papaya leaves had a significant effect (P < 0.05) on the weight gain of tilapia, but no significant effect (P > 0.05) on the survival rate. The best treatment was obtained at 7 days of fermentation, with an average weight gain of 19.53 g and a survival rate of 100%. Therefore, a fermentation duration of 7 days for papaya leaves in commercial feed is considered the most optimal time to enhance the growth of tilapia without affecting their survival rate.